A influência do julgamento do caso “Damião Ximenes Lopes versus Brasil” na corte interamericana de direitos humanos na reforma psiquiátrica brasileira - Lacerda, Athos Sartori (Universidade do Vale do Rio dos Sinos, 2020)
The present essay aims to identify if the judgment of the Case of Damião Ximenes Lopes versus Brazil in the Inter-American Court of Human Rights, in 2006, influenced the Brazilian Psychiatric Reform, which occurred in the country through Federal Law No. 10.216. The research was developed using the hypothetical deductive method. The research technique was bibliographic, with the study of doctrine, jurisprudence, scientific articles, scientific journals and other means that helped to deepen the case of Damião Ximenes Lopes, as well as about the Psychiatric Reform in Brazil. The method of procedure adopted was monographic. The case is important because it was the first time Brazil had a case judged internationally. Initially, it is explained to the reader the Inter-American Human Rights System and the handling of the case mentioned above. Afterwards, it is explained the history of the Anti-Asylum Movement and its consolidation through the Psychiatric Reform in Brazil. Finally, the last chapter is about the questioned influence, presenting the interfaces between the Damião Ximenes Lopes’s Case and the Brazilian Psychiatric Reform, as well as the challenges faced today for an effective concretization of human rights of psychiatric patients in the country.
Keywords: Direitos Humanos; Reforma psiquiátrica; Damião Ximenes Lopes; Sistema interamericano de direitos humanos; Human rights; Psychiatric reform; Damião Ximenes Lopes; Inter american human rights system